2017
DOI: 10.9790/1676-1201010105
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Dielectric Capacitance Determination from MetalInsulator-Semiconductor Devices Having Bias and Frequency Dependent Conductance Due To Leakage Current

Abstract: A model for MIS device in accumulation is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The current conduction through the SiO2 insulator and the oxide/semiconductor interface properties are the two groups of properties of a MOS device which are interrelated [4]. The current-voltage characterization of a MOS device in accumulation or inversion gives the properties of low-field leakage current through the oxide insulator, the onset electric field for Fowler-Nordheim (FN) tunnelling current, and the tunnelling current at high electric fields across the oxide insulator that leads to the breakdown of the oxide.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The current conduction through the SiO2 insulator and the oxide/semiconductor interface properties are the two groups of properties of a MOS device which are interrelated [4]. The current-voltage characterization of a MOS device in accumulation or inversion gives the properties of low-field leakage current through the oxide insulator, the onset electric field for Fowler-Nordheim (FN) tunnelling current, and the tunnelling current at high electric fields across the oxide insulator that leads to the breakdown of the oxide.…”
Section: Theorymentioning
confidence: 99%
“…It has been shown by the author in his earlier studies that the Einstein's mass-energy equivalence given by the equation E=mc 2 is manifested in semiconductors and insulators. It has been shown that the electron and hole effective masses in parabolic semiconductors and insulators are related to the intrinsic Fermi energy level in the bandgap of the materials by the universal mass-energy equivalence relation dE/E equals dm/m, where dE is the differential potential energy from the intrinsic Fermi energy level to the conduction band of the material, dm is the differential mass as the effective mass of carriers in the materials, E is the bandgap of the semiconductor or insulator as the total potential energy of the electrons, and m is the free electron mass [1]- [2]. This universal equation is obtained by differentiating Einstein's equation once on both sides and is valid for all energy transformations and moving big or small masses [3].…”
Section: Introductionmentioning
confidence: 99%